Carbon, nitrogen, phosphorus and potassium flows and losses from solid and semi-solid manures produced by beef cattle in deep litter barns and tied stalls. (February 2020) - Mathot, M.; Lambert, R.; Stilmant, D.; Decruyenaere, V.
Highlights: Even if uncertain, nutrient balances help in ranking nutrient losses. Nutrient losses from manure, in barns and under different manure storage conditions, vary strongly. Relations between nutrient losses and system parameters were established. Abstract: Nutrient losses have to be avoided in agricultural systems for agronomic and environmental reasons. However, they are known to be potentially large and variable. Results from twenty nine trials aiming at quantifying nitrogen (N), phosphorus (P), potassium (K) and carbon (C) flows and losses from barn and manure storage for beef cattle (Belgian Blue double-muscled breed) were synthesized. They included variation in barn type (tied stall and deep litter), leading to contrasted manure types (respectively semi-solid manure and deep litter manure) of small groups (n = 4) of heifers or bulls. Despite uncertainties pointed out by non-zero P or K balances, we established for manure storage, a relation between K losses by flowing out as liquid and rainfalls: K lost (%K stored) = 100*(1–0.99*e (−0.00078*rainfalls (mm)) ; n = 28). We also emphasized, within the particular set of data treated, the effects of barn type (approached by STRAWr; kg straw kg -1 DM in feed), manure storage duration (d), nitrogen in feed concentration (NFEED; g N kg -1 DM) and storage temperature (°C) on N losses from the whole system (N lost (% N input)=−33.33 + 0.0869*storage duration+1.11*storage temperature+27.9*STRAWr+1.278*NFEED; r² = 0.700; n = 29) such as the strong relation between C and N losses during manure store per day of storage (N lost (% N stored d -1 ) = 0.038 + 0.617*C lost (% C stored d -1 )). We also observed that, even if N and C inputs in the system were higher in deep litter systems due to straw supply, the amounts of N and C remaining in the manure after being stored were very similar, indicating higher losses of these nutrients from deep litter systems compared to tied stalls. These findings will further help in modeling cattle housing systems for nutrient cycling optimization. However, the relations established have to be validated for other tied stall and deep litter systems regarding the diversity in manure management for each barn type. Furthermore, when comparing manure provided under different housing systems, other agronomical (e.g. their sanitization due to heat increase when stored, ease of application to soil after storage) or environmental (e.g. greenhouse gas emissions) aspects have to be considered.